Tracheobronchopathia Osteochondroplastica: an uncommon aetiology for recurrent lower respiratory tract infection - Sabir, Mele Chelakkoth; Manappallil, Robin George; Babu, Harish; Mampilly, Neena (International Journal of Advances in Medicine, 2017)
Tracheobronchopathia Osteochondroplastica is a rare and benign condition characterised by development of osteocartilaginous nodules within the submuscosal layer of the trachea with sparing of the posterior wall. Majority of the patients remain asymptomatic throughout their lives unless severe airway obstruction develops; in which case patients present with symptoms such as dyspnoea, hoarseness of voice, persistent and often productive cough, haemoptysis, and pneumonia. This is the case of a middle-aged lady who presented with complaints of recurrent lower respiratory tract infection and was diagnosed to have tracheobronchopathia osteochondroplastica on computed tomography imaging, bronchoscopy and histopathological examination.